Preparation method and application of coal tar residue-based porous carbon sheet material

By making coal tar slag into porous carbon sheet materials, the problem of difficulty in effectively removing thallium in water in the prior art is solved, efficient and rapid adsorption effect is achieved, and high value-added utilization of coal tar slag is achieved.

CN119706835AInactive Publication Date: 2025-03-28HEFEI UNIV OF TECH +1

Patent Information

Application Number
CN202510213886.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art methods are difficult to effectively remove thallium (Tl(I)) in water, especially in terms of adsorbents with low cost, large output and stable source.

Method used

Coal tar residue is dissolved in an organic solvent for microwave-assisted extraction and separation, followed by ball milling with K3C6H5O7, and finally activated in an inert atmosphere, coal tar residue-based porous carbon sheet material was prepared. This material is used to adsorb T1(I) in wastewater.

Benefits of technology

The prepared coal tar slag-based porous carbon sheet material has efficient and fast adsorption ability, which can make the concentration of T1 (I) in the wastewater less than 5 μg/L, reach the emission standard, and at the same time achieve high added value utilization of coal tar slag, avoiding secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706835A_ABST
    Figure CN119706835A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a coal tar residue-based porous carbon sheet material, and relates to the technical field of solid waste utilization. According to the coal tar residue-based porous carbon sheet material, an organic reagent is used as an extracting agent, and oily components in coal tar residues are separated by adopting a microwave-assisted extraction method; the extracted coal tar residues and K3C6H5O7 are subjected to ball-milling mixing and then mildly activated in an inert atmosphere, and the K3C6H5O7 is obtained through washing, drying and grinding; and the coal tar residue-based porous carbon sheet material can be applied to treatment of Tl (I)-containing wastewater. The coal tar residue-based porous carbon sheet material prepared by the invention has an ultrahigh specific surface area and rich oxygen-containing functional groups, and shows efficient and rapid removal performance on Tl (I) in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste utilization, and in particular to a preparation method and application of a coal tar residue-based porous carbon sheet material. Background Art

[0002] Thallium (Tl) is a rare heavy metal with extremely high toxicity, bioaccumulation, neurotoxicity and immunotoxicity. Thallium exists in two valence states in aquatic environments: Tl (I) and Tl (III), of which Tl (I) is more stable. Thallium mainly exists in the Tl (I) valence state in nature. Due to the high toxicity of Tl (I) in industrial wastewater, the removal of Tl (I) in wastewater has become a key issue.

[0003] At present, the main methods for removing thallium from water include chemical precipitation, ion exchange, solvent extraction, biological method, membrane treatment and adsorption. Among them, adsorption is considered to be one of the main treatment technologies for thallium-containing wastewater because of its high efficiency, economy and simple operation. Many different types of adsorbents have been developed and applied to remove Tl (I) from water, including manganese dioxide-based, iron-based, aluminum-based, titanium-based, zinc-based and carbon-based materials. Porous carbon materials are considered to be an economical and effective material for treating thallium-containing wastewater due to their large specific surface area, developed pore structure and stable properties. The key to porous carbon adsorption technology is to find carbon precursors with low cost, high yield and stable source.

[0004] Coal tar residue is a brown viscous solid waste produced during the coking process. It has the characteristics of high fixed carbon, high volatile matter and low ash content, but its polycyclic aromatic hydrocarbons content is high. Direct use of coal tar residue has poor environmental benefits. In contrast, removing tar from coal tar residue by centrifugal separation, pyrolysis separation or extraction separation can reduce environmental risks, and then using it as a precursor to produce porous carbon is a high value-added utilization approach. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a coal tar residue-based porous carbon sheet material and its application. The porous carbon sheet material has the characteristics of mild and simple manufacturing process, low cost, large specific surface area, fast adsorption speed of Tl (I) in wastewater, and good adsorption performance.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions: A method for preparing a coal tar residue-based porous carbon sheet material, the preparation method comprising the following steps: (1) dissolving coal tar residue in an organic solvent and separating the oily components by microwave-assisted extraction to obtain pretreated coal tar residue; (2) Mix the above pretreated coal tar residue with K 3 C 6H 5 O 7 Ball milling is performed to obtain a mixed material for use; (3) The mixed material is placed in a tubular furnace, heated and activated in an inert atmosphere, and then washed, dried and ground to obtain a coal tar residue-based porous carbon sheet material.

[0007] Preferably, the organic solvent in step (1) is any one of n-hexane, cyclohexane, 1,4-dioxane, benzene, dimethyl carbonate, ethyl acetate, ethanol, methanol and acetonitrile.

[0008] Preferably, the temperature of the microwave-assisted extraction in step (1) is 50-75° C. and the time is 4-15 min.

[0009] Preferably, in step (2), the coal tar residue and K are pretreated 3 C 6 H 5 O 7 The mass ratio is 1:1-4.

[0010] Preferably, the temperature for heating and activating in step (3) is 700-900° C., and the activation time is 1-3 h.

[0011] The coal tar residue-based porous carbon sheet material prepared above is used for static or dynamic adsorption of Tl (I) in wastewater.

[0012] Preferably, during the static adsorption of Tl (I) in wastewater, the input amount of coal tar residue-based porous carbon sheet material is 0.1-1.5 g / L, the pH of the wastewater is 2-12, the static adsorption time is 1-720 min, the initial concentration of Tl (I) is 7.5-400 mg / L, and the adsorption temperature is 15-35°C.

[0013] Preferably, the dynamic adsorption of Tl (I) in wastewater adopts fixed bed adsorption, and the inlet flow rate of the wastewater is controlled to be 1.0-2.0 mL / min, the fixed bed height is 4-8 mm, and the initial concentration of Tl (I) is 7.5-30 mg / L.

[0014] The coexisting ions in the wastewater are K + 、Na + , Ca 2+ , Cl - 、F - , and the coexisting ion concentration is 0.1-0.001 mol / L, and there may also be coexisting organic matter in the wastewater, the coexisting organic matter is humic acid and / or EDTA-2Na, and the coexisting organic matter concentration is 1-0.01 mmol / L.

[0015] The present invention provides a method for preparing a coal tar residue-based porous carbon sheet material and its application, which has the following advantages over the prior art: (1) The raw material of the porous carbon sheet material prepared by the present invention is solid waste coal tar residue, which is converted into an environmental functional material, thus realizing high added value utilization of coal tar residue; (2) The porous carbon sheet material prepared by the present invention has a mild and simple synthesis method, low cost, large specific surface area, and can be used to remove Tl (I) from wastewater without causing secondary pollution; (3) The porous carbon sheet material has a high efficiency and rapid adsorption capacity for Tl(I) in wastewater, which can reduce the Tl(I) concentration to less than 5 μg / L and meet the discharge standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the porous carbon sheet prepared in Example 1 of the present invention; Figure 2 The nitrogen adsorption-desorption curve and pore size distribution diagram of the coal tar residue-based porous carbon sheet prepared in Example 1 of the present invention; Figure 3 This is a Fourier transform infrared spectrum of the coal tar residue-based porous carbon sheet prepared in Example 1 of the present invention; Figure 4 It is a schematic diagram of the adsorption performance of the porous carbon sheet on Tl (I)-containing wastewater under different addition amounts in Example 2; Figure 5 Schematic diagram of the adsorption performance of the porous carbon sheet for Tl (I)-containing wastewater under different pH conditions for 720 min in Example 3; Figure 6 The effect of different ions or organic matter at different contents in wastewater on the adsorption of Tl (I) by porous carbon sheets in Example 4, where (a) is the K content of porous carbon sheets at different contents in wastewater in Example 4. + 、Na + , Ca 2+ 、F - or Cl - (b) is a schematic diagram of the adsorption amount of Tl (I) by the porous carbon sheet in Example 4 under different contents of humic acid or EDTA-2Na in wastewater; Figure 7 (a) is a schematic diagram of the adsorption performance of the porous carbon sheet at different times when the concentration of the wastewater containing Tl (I) in Example 5 is 7.5 mg / L; (b) is a schematic diagram of the adsorption performance of the porous carbon sheet at different times when the concentration of the wastewater containing Tl (I) in Example 5 is 15 mg / L; Figure 8(a) is a schematic diagram of the dynamic adsorption performance of the porous carbon sheet for Tl (I)-containing wastewater under different water inlet flow rates in Example 6; (b) is a schematic diagram of the dynamic adsorption performance of the porous carbon sheet for Tl (I)-containing wastewater under different fixed bed heights; (c) is a schematic diagram of the dynamic adsorption performance of the porous carbon sheet for Tl (I)-containing wastewater under different Tl (I) initial concentrations. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Embodiment 1: Preparation of coal tar residue-based porous carbon sheet materials: Coal tar residue was dissolved in benzene at a volume mass ratio of 5 mL / g, and the oily components were separated by microwave-assisted extraction at 75 °C for 10 min. 3 C 6 H 5 O 7 Ball milling was performed at a mass ratio of 1:3 g / g to form a mixed material. The mixed material was then placed in a tubular furnace and gently activated at 700°C for 2 h under an inert atmosphere. A porous carbon sheet was obtained after washing, drying and grinding.

[0019] The obtained porous carbon sheet was examined by scanning electron microscopy and transmission electron microscopy. The SEM and TEM images are shown in Figure 1 Shown: K 3 C 6 H 5 O 7 During the activation process, K 2 CO 3 Etching precursors, and can act as templates to promote the formation of carbon sheets. Because the SEM images of coal tar residue-based porous carbon sheet materials show interlinked flake structures of different sizes. This interlinked flake structure can provide sufficient adsorption sites during the adsorption process. TEM images show that coal tar residue-based porous carbon sheet materials have a clear layered structure.

[0020] The prepared porous carbon sheet was subjected to nitrogen adsorption and desorption test. The adsorption and desorption curves of the material and the DFT pore size distribution curves are shown in Figure 2 As shown: The nitrogen adsorption-desorption curve of the prepared porous carbon sheet is a composite I / IV curve. When the relative pressure is less than 0.1, the curve rises steeply, and when the relative pressure is greater than 0.4, a hysteresis loop appears, indicating that there are a large number of microporous structures and some mesopores in the material.

[0021] The pore size of the porous carbon sheet is mainly distributed in the range of 0.5-1.0 nm. The specific surface area of ​​the porous carbon sheet is 3034 cm 2 / g, and the specific surface area of ​​micropores is 2708 cm 2 / g, and a volume of 1.492 cm 3 / g, and the average pore size is 1.967 nm.

[0022] The prepared porous carbon sheet was subjected to Fourier transform infrared spectroscopy. Figure 3 As shown: The porous carbon sheets contain a variety of oxygen-containing functional groups.

[0023] Embodiment 2: The porous carbon sheet material prepared in Example 1 was added to the wastewater containing Tl (I) for static adsorption in a full-temperature oscillator. The static adsorption conditions were that the concentration of Tl (I) in the wastewater was 7.5 mg / L, the pH was 6, the amount of the porous carbon sheet material added was 0.1-1.5 g / L, and the oscillation speed was 240 rpm at 25°C for 720 min. The removal performance of Tl (I) was shown in FIG. Figure 4 .

[0024] from Figure 4 It can be seen that the coal tar residue-based porous carbon sheet material has a good removal performance for Tl (I) in wastewater. Even when the addition amount is 0.1 g / L, the removal rate can reach 85.49% for the Tl (I) solution with an initial concentration of 7.5 mg / L. The optimal addition amount is 0.5 g / L, at which time, the removal rate can reach 99.54%.

[0025] Embodiment 3: The porous carbon sheet material prepared in Example 1 was added to the wastewater containing Tl (I) for static adsorption. The dosage was 0.5 g / L, the initial concentration of Tl (I) was 7.5 mg / L, the pH of the wastewater containing Tl (I) was 2-12, and the carbon sheet material was oscillated at 240 rpm for 720 min at 25°C. The removal performance of Tl (I) was as follows: Figure 5 The adsorption rate and amount of Tl (I) on the coal tar residue-based porous carbon sheet increased first and then stabilized with the increase of pH, reaching the highest value at pH 6, at which the adsorption rate was 99.54%.

[0026] Embodiment 4: The porous carbon sheet material prepared in Example 1 was added to the wastewater containing Tl (I), the dosage was 0.5 g / L, the initial concentration of Tl (I) was 7.5 mg / L, the pH of the wastewater containing Tl (I) was 6, and a single variable experiment was set to set the wastewater to contain different ions (K + 、Na + , Ca 2+ 、F - or Cl - ), or different concentrations (1 mmol / L-0.001 mmol / L) of organic matter (fulvic acid or EDTA-2Na), were shaken at 240 rpm for 720 min at 25 °C. The adsorption of Tl (I) was shown in Figure 6 .

[0027] Depend on Figure 6 (a) It can be seen that when K exists in wastewater + 、Na + , Ca 2+ 、F - or Cl - The adsorption of Tl(I) by coal tar residue-based porous carbon sheets was inhibited to varying degrees, among which 0.1 mol / L K + The inhibitory effect is most obvious. Figure 6 (b) It can be seen that when fulvic acid or EDTA-2Na exists in the wastewater, it will have a slight inhibitory effect on the adsorption of Tl (I) in the wastewater by the coal tar residue-based porous carbon sheet. When the concentration of fulvic acid is 1 mmol / L, the inhibitory effect is most obvious, but the adsorption amount of Tl (I) by the overall porous carbon sheet material is still high.

[0028] Embodiment 5: The coal tar residue-based porous carbon sheet material prepared in Example 1 was added to the wastewater containing Tl (I), the dosage was 0.5 g / L, the initial concentration of Tl (I) was 7.5 mg / L, the pH of the wastewater containing Tl (I) was 6, and the material was shaken at 240 rpm for 1-720 min at 25 ° C. The removal performance of Tl (I) was as follows: Figure 7 .

[0029] It can be seen that the coal tar residue-based porous carbon sheet material has a rapid adsorption capacity for Tl (I) in wastewater. Within the first 1 minute, the removal rates of Tl (I) with initial concentrations of 7.5 mg / L and 15 mg / L can reach 92.67% and 82.96%, respectively. The adsorption basically reaches equilibrium within 90 minutes, at which time the removal rates of Tl (I) with initial concentrations of 7.5 mg / L and 15 mg / L can reach 99.32% and 95.79%, respectively.

[0030] Embodiment 6: 0.1-0.2 g of the porous carbon sheet prepared in Example 1 was loaded into a plexiglass column with an inner diameter of 9 mm and a length of 10 cm. Wastewater containing Tl(I) with an initial concentration of 7.5-30 mg / L was injected into the plexiglass column from the lower end using a peristaltic pump, and the inlet volume flow rate was 1.0-2.0 mL / min. The Tl(I) concentration in the outflowing wastewater was detected at regular intervals. The results are shown in Table 1. Figure 8 .

[0031] When the treatment target is 2 μg / L, 0.1 g of coal tar-based porous carbon sheet material can treat at most 0.12 L of wastewater containing Tl (I) with a concentration of 7.5 mg / L. When the treatment target is 5 μg / L, 0.1 g of coal tar-based porous carbon sheet material can treat at most 0.4 L of wastewater containing Tl (I) with a concentration of 7.5 mg / L.

[0032] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a coal tar residue-based porous carbon sheet material, characterized in that: The preparation method comprises the following steps: (1) dissolving coal tar residue in an organic solvent and separating the oily components by microwave-assisted extraction to obtain pretreated coal tar residue; (2) The pretreated coal tar residue is mixed with K3C6H5O7 and ball-milled to obtain a mixed material for later use; (3) The mixed material is placed in a tubular furnace, heated and activated in an inert atmosphere, and then washed, dried and ground to obtain a coal tar residue-based porous carbon sheet material.

2. The preparation method according to claim 1, characterized in that: The organic solvent in step (1) is any one of n-hexane, cyclohexane, 1,4-dioxane, benzene, dimethyl carbonate, ethyl acetate, ethanol, methanol and acetonitrile.

3. The preparation method according to claim 1, characterized in that: The temperature of the microwave-assisted extraction in step (1) is 50-75° C. and the time is 4-15 min.

4. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the pretreated coal tar residue to K3C6H5O7 is 1:1-4.

5. The preparation method according to claim 1, characterized in that: The temperature for heating and activating in step (3) is 700-900° C., and the activation time is 1-3 hours.

6. A coal tar residue-based porous carbon sheet material prepared by any of the methods of claims 1 to 5 for use in static or dynamic adsorption of Tl (I) in wastewater.

7. The use according to claim 6, characterized in that: During the static adsorption of Tl (I) in wastewater, the input amount of coal tar residue-based porous carbon sheet material is 0.1-1.5 g / L, the pH of the wastewater is 2-12, the static adsorption time is 1-720 min, the initial concentration of Tl (I) is 7.5-400 mg / L, and the adsorption temperature is 15-35°C.

8. The use according to claim 6, characterized in that: The dynamic adsorption of Tl (I) in wastewater adopts fixed bed adsorption, and the inlet flow rate of the wastewater is controlled to be 1.0-2.0 mL / min, the fixed bed height is 4-8 mm, and the initial concentration of Tl (I) is 7.5-30 mg / L.

Citation Information

Patent Citations

  • Method for preparing activated carbon from coal tar residues and application thereof

    CN103626175A

Cited By

  • Method for preparing activated carbon from tar residue and coal powder

    CN122685067A

  • A method for preparing activated carbon using tar residue and coke powder

    CN122704915A

  • A method for preparing activated carbon from tar residue and sludge

    CN122748643A